IMPLEMENTATION OF DIRECT INSTRUCTION IN MATHEMATICS CLASSROOMS DURING THE NEW NORMAL: IMPLEMENTASI PEMBELAJARAN LANGSUNG DALAM PEMBELAJARAN MATEMATIKA SELAMA ERA NEW NORMAL - Fadhil Zil Ikram; Rosidah (MaPan : Jurnal Matematika dan Pembelajaran, 2023)
The development of the covid-19 vaccine and the impact of online learning enable the government in Indonesia to remove some restrictions caused by the pandemic and our situation now is called the new normal. In the sector of education, some schools already implemented PTMT (Pembelajaran Tatap Muka Terbatas) by fully implementing face-to-face learning with some restrictions recommended by the government. One of the learnings that most teachers used was direct instruction. This study employed a sequential explanatory design to investigate the implementation of direct instruction in mathematics classrooms during the new normal. Firstly, we measured the effectiveness of direct instruction. Secondly, we investigated the factors affecting the results of our measurement of learning effectiveness. Two classes of the eleventh grade in one of the high schools in Makassar were chosen as the sample of our study. The findings of our study imply that the implementation of direct instruction in the mathematics classroom is not effective during the new normal based on the mathematics test results of the students. However, students and teachers respond positively to the implementation of direct instruction in mathematics lessons during the new normal. Our interview results reveal several factors causing the ineffectiveness, which were lesson duration, the number of tasks, and the short deadline of tasks from other subjects. Thus, the students cannot focus and overlook mathematics because they shift their focus to other subjects.